2008
DOI: 10.1128/mcb.01665-07
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Fbxw8 Gene Results in Pre- and Postnatal Growth Retardation in Mice

Abstract: CUL7 binds to SKP1, RBX1, and FBXW8 to form a cullin-RING ligase, or an SKP1-cullin-F box protein complex. The targeted disruption of the Cul7 gene in mice results in significant reduction in embryo size and neonatal lethality. In humans, CUL7 was found to be mutated in the 3-M dwarfism syndrome characterized by severe pre-and postnatal growth retardation, indicating that CUL7 is closely associated with human and mouse growth. We generated mice lacking Fbxw8 by gene trapping. Similar to Cul7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 36 publications
3
48
1
Order By: Relevance
“…In addition to possible GH/IGF resistance, dysregulation of IGFBP2 and IGFBP5 had previously been identified (Huber et al 2010) with downregulation of IGFBP2 and upregulation of IGFBP5 expression seen in fibroblasts from two patients with OBSL1 mutations. By contrast, upregulation of IGFBP2 is seen in the Cul7 K/K mouse (Tsutsumi et al 2008). We now demonstrate that regardless of mutation status, all 3-M cell lines show reduced secreted protein levels of IGFBP2 and -7.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to possible GH/IGF resistance, dysregulation of IGFBP2 and IGFBP5 had previously been identified (Huber et al 2010) with downregulation of IGFBP2 and upregulation of IGFBP5 expression seen in fibroblasts from two patients with OBSL1 mutations. By contrast, upregulation of IGFBP2 is seen in the Cul7 K/K mouse (Tsutsumi et al 2008). We now demonstrate that regardless of mutation status, all 3-M cell lines show reduced secreted protein levels of IGFBP2 and -7.…”
Section: Discussionmentioning
confidence: 98%
“…In clinical reports, there are little, if any, data on the status of the GH-IGF axis in 3-M patients, nor are there data on the degree of height restriction by mutation type. We do, however, know that IGFBP gene expression is abnormal in cells derived from 3-M patients (Huber et al 2010) and in the Cul7 K/K mouse (Tsutsumi et al 2008). This study has addressed the following: i) identification and frequency of mutations in the three genes in those with a clinical diagnosis of 3-M; ii) height at presentation, the status of the GH-IGF axis as measured in serum assays by mutation status and IGFBP generation from cultured cell lines; and iii) in view of the relative clinical resistance to GH treatment and involvement of IRS1, MAPK and AKT, an assessment of the activation of signalling pathways by GH and IGF1.…”
mentioning
confidence: 99%
“…Fbxw8 –/– mice have a reduced placental size but appear to have no isolated placental abnormalities. Tsutsumi et al [33] confirmed the Fbxw8 –/– phenotype and underlined the similarities between Fbxw8 –/– and Cul7 –/– mice. Growth restriction of Fbxw8 –/– mice continued postnatally, but the mice were otherwise normal.…”
Section: Cul7 and The Ubiquitin-proteasome Pathwaymentioning
confidence: 50%
“…Growth restriction of Fbxw8 –/– mice continued postnatally, but the mice were otherwise normal. Arai et al [31] established that Fbxw8 protein levels were reduced in Cul7 –/– cells, with Tsutsumi et al [33] demonstrating that Cul7 levels were also reduced in Fbxw8 –/– mouse embryonic fibroblast (MEF) cells. Fbxw8 –/– MEFs grew very poorly when compared to Fbxw8 +/– or Fbxw8 +/+ MEFs.…”
Section: Cul7 and The Ubiquitin-proteasome Pathwaymentioning
confidence: 99%
“…The 26S proteasome, which regulates the proteolytic activity of the matrix metalloproteinases (MMPs)-2 and -9, is required during implantation process (Wang et al 2004). The important function of other ubiquitination-related proteins such as the Ub-conjugating enzyme UBCM4 (Harbers et al 1996), the proteasome activator PSME3 (PA28g; Murata et al 1999), Ub ligase CUL7 (Huber et al 2005) and FBXW8 (Tsutsumi et al 2008) was demonstrated by the phenotype of mouse models with placenta and intrauterine embryonic growth retardation. The Smurf2 gene, encoding E3 class protein, is involved in trophoblast cell invasion and embryo implantation (Yang et al 2009).…”
Section: Introductionmentioning
confidence: 99%